Regulation and Market Liquidity - Trebbi, Francesco; Xiao, Kairong (Management Science, 2017)
We examine the effects of postcrisis financial regulation, encompassing the Dodd–Frank Act and Basel III, on market liquidity of the U.S. fixed-income market. We estimate structural breaks in a large panel of liquidity measures of corporate and Treasury bonds. Our methodology does not require a priori knowledge of the timing of breaks, can capture not only sudden jumps but also breaks in slow-moving trends, and displays excellent power properties. Against the popular claim that postcrisis regulation hurt liquidity, we find no evidence of liquidity deterioration during periods of regulatory intervention. Instead, breaks toward higher liquidity are often detected. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2876.